Tolerability of BRAF and MEK inhibitors for metastasized melanoma after intra-class switch: a multicenter, retrospective study - Salzmann, Martin; Wald, Alexander; Stege, Henner; Loquai, Carmen; Zimmer, Lisa; Hayani, Kinan M.; Heinzerling, Lucie; Gutzmer, Ralf; Enk, Alexander; Hassel, Jessica C. (Cancers, 2023)
Patients suffering from metastasized melanoma can be treated with three different combinations of tablets (“targeted therapy”), with similar efficacy but different side effect profiles. When one of the combinations is not tolerated well, their physicians may switch to a different combination; however, it has not been evaluated whether the second combination is actually tolerated better. ...
Gesehen am 07.12.2023